Cultivation and Processing of Aloe Vera to Enhance Community Income - Siti Asriah Immawati; Rosyid Rosyid; Humairoh Humairoh; Yudhi Rahman (Jurnal Pengabdian Masyarakat dan Penelitian Thawalib, 2025)
Aloe vera is a versatile plant with numerous health and beauty benefits; however, its cultivation potential has not been fully optimised due to residents' limited knowledge and skills in both cultivation and processing. The cultivation and processing of aloe vera in RW 06, Gandasari Subdistrict, Jatiuwung District, Tangerang City, was carried out to increase community income. The methodology employed was Participatory Action Research (PAR), involving stages such as socialisation, training on cultivation and processing, provision of resources, technical assistance, and marketing strategies based on local needs. The results of the community service program indicated several stages of implementation. Land preparation for aloe vera cultivation involved weeding, loosening the soil to 30–50 cm depth, and allowing it to rest for 1–2 weeks. Soil was treated 2–3 times with the addition of fertilisers, followed by the construction of planting beds 100–120 cm wide and 20–25 cm high. Seedlings were planted at a 5–7 cm depth with spacing of either 50 x 75 cm or 50 x 100 cm. A survey of 10 respondents revealed that 60% successfully produced aloe vera gel and 50% attempted to make healthy beverages. The program received positive feedback, with 88% of participants understanding the benefits, 90% reporting that they were supported by providing seedlings and tools, and 70% understanding marketing strategies, indicating overall training success. Conclusion: The program had a positive impact, as the community successfully engaged in aloe vera cultivation, supported the local economy, and contributed to creating new job opportunities.